THE RELATIONSHIP AMONG STAKE-HOLDER IN DEVELOPING RUBBER INDUSTRIAL CLUSTER IN SOUTH SUMATRA - Dian Novriadhy (Pusbindiklat - LIPI, 2012)
This research aims to determine the relationship among stake-holder in the effort of developing rubberindustry cluster in South Sumatra. The research method is carried out by identifying the relationships amongstake-holders, policies and regulations that support the development of rubber industrial cluster, and theirimplementation. The results indicate there is not any relationship among stake-holders. Nevertheless, policies andregulations give significant effect to the development of rubber industry in South Sumatra.